P06.15 The stability of the vaginal microbiome in relation to new sexual experiences. (13th September 2015) - Twin, J; Bradshaw, CS; Vodstrcil, LA; Garland, SM; Fairley, CK; Fehler, G; Hocking, JA; Law, M; Fethers, KA; Tabrizi, SN
Abstract : Introduction: The vaginal microbiome in healthy asymptomatic women can vary greatly, though in most is typically dominated by lactic acid producing Lactobacillus spp. which convey protection against pathogens. Few studies have examined genital bacterial communities in sexually-inexperienced women over time and particularly changes occurring upon initiation of new sexual experiences. Methods: Overall192 samples from 45 healthy women were selected as a subset of a study investigating the sexual health of 17–21 year old university students. Women who were selected included those with no previous sexual experience (n = 17), women experienced in non-coital sexual activities only (n = 15) and women who had engaged in penile-vaginal sex (n = 13). The selected participants provided self-collected vaginal swab samples every 3 months for 12 months. Bacterial communities were analysed using Roche 454 amplicon sequencing with PCR primers targeting the V3/4 variable region of the 16S rRNA gene. Results: Overall, healthy young women had differing vaginal community states. Onset of non-coital and coital sexual activities does not exert a significant effect on the composition of vaginal bacterial communities. The vaginal community-state with the greatest stability over time consisted of states predominated by L. crispatus and L. iners with median Bray-curtis dissimilarity values of 12.4 and 17.6 respectively (p = 0.005 and 0.024). Vaginal microbiomes dominated by other Lactobacillus spp. and non- Lactobacillus spp. gave rise to the most variability over time (dissimilarity values of 41.1 and 66.8). Non-coital and coital sexual activity within this subset of participants did not have any significant effect upon the stability of vaginal bacterial communities (p = 0.3714). Conclusion: L. crispatus and L. iners are most commonly found to dominate sexually inexperienced women and convey the most stable environment over time. The initiation of new sexual activities does not appear to have any persistent effect on the vaginal microbiome of young women. Disclosure of interest statement: None to declare.